The impact of kinetic parameters on cellulose hydrolysis rates. (November 2018) - Nill, Jennifer; Karuna, Nardrapee; Jeoh, Tina
Highlights: Variations in rate constant estimates affect the outcome of hydrolysis predictions. Burst phase kinetics are only observed at enzyme-limiting conditions. Low abundance of productive binding sites limit initial cellulose hydrolysis rates. Abstract: Mechanistic kinetic models are vital tools to elucidate rate-limiting interactions and processes hampering complete hydrolysis of cellulose by cellulases. Properly formulated, the models should ultimately simulate experimental cellulose hydrolysis time courses given that model parameters are known a priori . Here, we review reported values of critical parameters in cellulose hydrolysis (catalytic, adsorption/desorption, complexation/decomplexation rate constants and apparent processivity) and examine how estimation methods may impact the magnitudes and interpretation of the values. The sensitivity of the extents and rates of cellulose hydrolysis to the range of reported values were examined by conducting simulations with a general mechanistic model of Tr Cel7A hydrolysis of cellulose. When the simulation was conducted at enzyme-limiting conditions, initial bursts in cellulose hydrolysis rates were evident and highly sensitive to specific hydrolysis rates of productively bound enzymes and dissociation rates of non-productively bound enzymes. Under substrate limiting conditions, hydrolysis rates were significantly reduced and no initial burst was observed, with more pronounced sensitivity of hydrolysis rates to the range of kinetic values. Enzyme-substrate interaction rate constants reviewed here only capture short-time hydrolysis rate outcomes and future work to elucidate mechanisms of cellulose hydrolysis must also incorporate how substrate-limitations evolve over the course of hydrolysis.